2021
DOI: 10.1111/add.15630
|View full text |Cite
|
Sign up to set email alerts
|

An intensive model of care for hepatitis C virus screening and treatment with direct‐acting antivirals in people who inject drugs in Nairobi, Kenya: a model‐based cost‐effectiveness analysis

Abstract: Background and aims Hepatitis C virus (HCV) treatment is essential for eliminating HCV in people who inject drugs (PWID), but has limited coverage in resource-limited settings. We measured the cost-effectiveness of a pilot HCV screening and treatment intervention using directly observed therapy among PWID attending harm reduction services in Nairobi, Kenya. Design We utilized an existing model of HIV and HCV transmission among current and former PWID in Nairobi to estimate the cost-effectiveness of screening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In the early days of HIVST research, modelling studies predicted that HIVST would be cost-effective [12] and subsequent studies confirmed this. Cost-effectiveness studies of HIVST in LMIC also found the introduction of self-testing led to increased diagnosis and linkage to care, but with an additional cost to identify each case [17,26]. The first HCVST real world implementation studies are currently underway, piloting different models of HCVST distribution in Malaysia and Pakistan[14, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early days of HIVST research, modelling studies predicted that HIVST would be cost-effective [12] and subsequent studies confirmed this. Cost-effectiveness studies of HIVST in LMIC also found the introduction of self-testing led to increased diagnosis and linkage to care, but with an additional cost to identify each case [17,26]. The first HCVST real world implementation studies are currently underway, piloting different models of HCVST distribution in Malaysia and Pakistan[14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…These additional costs need to be minimised through ensuring that test costs are kept low and linkage to care rates are high. [24,26,30]) and have sensitivity and specificity of 100% as they are the gold standard against which the RDTs are compared.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HCV testing needs expanding to allow HCV treatment scale-up; only 22% of PWID in 2015 reported being tested for HCV in last 3 months compared with 74% for HIV [ 7 ]. This testing could occur when HIV testing occurs through NSP or OAT clinics as demonstrated by two pilot HCV screening and treatment interventions in Kenya [ 16 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following HCV infection, some PWID spontaneously clear infection (differs by HIV infection), with the remainder progressing to chronic infection. Chronically infected PWID can receive HCV treatment, with most (90.1% [ 16 ]) achieving a sustained virologic response (SVR). Those not achieving SVR return to the chronically infected compartment and are eligible for re-treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation